Influence of the Conditions of Sensitization on the Characteristics of p-DSCs Sensitized with Asymmetric Squaraines. Issue 14 (7th December 2017) - Bonomo, M.; Saccone, D.; Magistris, C.; Barolo, C.; Ciná, L.; Carlo, A. Di; Dini, D.
Abstract : The effect of the conditions of sensitization on the photoelectrochemical performance of p -type dye-sensitized solar cells ( p -DSCs) with screen-printed nickel oxide (NiO) photocathodes is analyzed. The dye-sensitizers employed in the present study are asymmetric squaraines. The conditions of sensitization differ for the relative concentration of the anti-aggregating agent CDCA (chenideoxycholic acid) with respect to the concentration of the dye-sensitizer. The co-adsorption of CDCA onto NiO electrode brings about a decrease in the surface concentration of the anchored dye as well as a blueshift of the characteristic wavelengths of optical absorption of the asymmetric squaraines considered here. Beside this, the employment of CDCA as co-adsorbent reduces the overall conversion performance of the resulting squaraine-sensitized p -DSCs with consequent diminution of the short-circuit current density. This result is ascribed to the acid action of CDCA toward the amminic nitrogen of the squaraines. Quantum efficiency spectra show that CDCA acts as a quencher of the intrinsic photoelectrochemical activity of NiO. Moreover, CDCA does not interfere with the mechanism of charge injection effectuated by the photoexcited squaraines. The photoelectrochemical impedance spectra was analyzed employing a model of equivalent circuit developed for semiconducting nanostructure electrodes.